Perceptions of preoperative expectations and postoperative outcomes from orthognathic surgery: Part I: Turkish female patients - VAROL, ALTAN (CHURCHILL LIVINGSTONE, 2008)
This Study was conducted in Turkish female patients to investigate their preoperative concerns, motivation, expectations, preoperative preparation for surgery and perception of outcomes concerning orthognathic surgery. Thirty women, with an age range of 18 to 31 years (mean age 21.8 +/- 3.8 years), participated in the study. The expectations and the results of orthognathic treatment were assessed based on the patients' Subjective appraisal. Patients completed questionnaires before and after the operations, designed to investigate the preoperative and postoperative psychological impact of the surgery, the perception of problems with physical and psychological functioning, self-image, body image and satisfaction with surgical outcome. The questionnaires were evaluated statistically with SPSS 11.5 for Windows. The patients' perception of their psychological improvement, faith in the surgical team, physical functioning, self-esteem, social confidence, body image and satisfaction after dentofacial correction were higher than the preoperative levels. The conclusions of the study support the theory that enhancement of facial appearance by orthognathic Surgery improves the psychological status of females with growth disturbances of the jaw.
Keywords: psychological assessment; orthognathic surgery; preoperative/postoperative perception; female patients; OF-LIFE MEASURE; DENTOFACIAL DEFORMITY; SURGICAL-CORRECTION; CONVENTIONAL ORTHODONTICS; PROGNATHISM; IMPACT; TERM